Determination of Antioxidants in Smilacis Glabrae Rhizoma by High-Performance Liquid Chromatography with Ultraviolet and Mass Spectrometry Detection. (1st September 2016) - Zhang, Zhi-feng; Lu, Lu-yang; Liu, Yuan; Zeng, Rui; Xie, Jing; Huang, Ye-qing; Shen, Qing; Cheung, Hon-yeung
ABSTRACT: Smilacis Glabrae Rhizoma is a traditional food in China. Although phytochemical and pharmacology studies have been performed, the antioxidant constituents have not been characterized with the exception of astilbin. In the present study, six antioxidants in Smilacis Glabrae Rhizoma were determined by high-performance liquid chromatography with ultraviolet and mass spectrometry detection using 1, 1-diphenyl-2-picrylhydrazyl and 2, 2′-azinobis (3-ethylbenzthiazoline-6-sulfonic acid) assays. These analytes were 5- O -caffeoylshikimic acid, polydatin, neoastilbin, astilbin, neoisoastilbin, and isoastilbin. The relative Trolox equivalent antioxidant capacity of each compound was determined using the two protocols. Moreover, antioxidant fingerprints were constructed for quality evaluation of Smilacis Glabrae Rhizoma and principal component analysis was performed to provide a guide for customers and producers to ensure the quality of the raw materials. The methodology may be used for the analysis of Smilacis Glabrae Rhizoma and potentially for other plant-based products.